AIDS-Orphanhood and Caregiver HIV/AIDS Sickness Status: Effects on Psychological Symptoms in South African Youth - Cluver, L.; Orkin, M.; Boyes, Mark; Gardner, F.; Nikelo, J. (Oxford University Press, 2012)
Objective: Research has established that AIDS-orphaned youth are at high risk of internalizing psychological distress. However, little is known about youth living with caregivers who are unwell with AIDS or youth simultaneously affected by AIDS-orphanhood and caregiver AIDS sickness. Methods: 1025 South African youth were interviewed in 2005 and followed up in 2009 (71% retention). Participants completed standardized measures of anxiety, depression, and posttraumatic stress. Comparison groups were youth who were AIDS-orphaned, other-orphaned, and nonorphaned, and those whose caregivers were sick with AIDS, sick with another disease, or healthy. Results: Longitudinal analyses showed that both AIDS-orphanhood and caregiver AIDS sickness predicted increased depression, anxiety, and posttraumatic stress symptoms over a 4-year period, independently of sociodemographic cofactors and of each other. Caregiver sickness or death by non-AIDS causes, and having a healthy or living caregiver, did not predict youth symptomatology. Youths simultaneously affected by caregiver AIDS sickness and AIDS-orphanhood showed cumulative negative effects. Conclusions Findings suggest that policy and interventions, currently focused on orphanhood, should include youth whose caregivers are unwell with AIDS.